The effect of social media, online review, and price discount on impulse buying - Fradia, Redha; Yasri, Yasri (Universitas Negeri Padang, 2024)
The purpose of this study was to analyze the effect of social media on impulse buying, to analyze online reviews on impulse buying, and to analyze the effect of price discounts on impulse buying. the population of this study were Padang City students who used the Shopee application. The research sample is 180 respondents. Purposive sampling was the method employed, and the only requirements were that the participants be students from Padang City and have purchased items through the Shopee app. Multiple linear regression analysis is the method utilized for data analysis. The findings demonstrated that social media significantly and favorably influences impulsive buying. Impulsive buying are significantly and favorably impacted by online reviews. Discounts significantly and favorably influence impulsive buying.